Fostering environmental awareness through story reading (Eurasian Journal of Philology Science and Education, 2018)
The article considers the effective ways of inculcating environmental awareness through foreign language learning. Integration of environmental topics into language learning process can be very useful for developing both language and content knowledge. Teaching language simultaneously with environmental issuesenables students to enhance their abilities for critical thinking and to develop their communicative competence.This paper focuses on developing ecological awareness through environmental story reading activity.Story reading helps students to think critically about what they have read, discuss their opinions, understand their social functions and develop as responsible citizens.Besides, story reading activity is a powerful source of developing reading, retelling, translating and word enrichment skills.